POWER RELATIONS IN THE TAMBLINGAN INSCRIPTION IN THE X-XIV CENTURY AD - Utami, Luh Suwita; Ardika, I Wayan; Suastika, I Made (E-Journal of Cultural Studies, 2021)
The king, as the ruler of a region, in the past published inscriptions that functioned as a tool in disputing his power. The inscription contains a discourse about granting rights by the king or high-ranking royal officials to a group of residents in an area. In the X-XIV centuries AD in Bali, a number of inscriptions were published for the Balinese who lived in Tamblingan. This inscription tells about various obligations, taxes, social rules and curses to the people in Tamblingan issued by the kings.This study aims to determine the form of power relations, ideological elements, and implications of power relations contained in the ancient Balinese inscriptions of the X-XIV centuries AD related to the Tamblingan area. The data collection method used in this research is a literature study of the inscriptions published in the X-XIV centuries AD related to the Tamblingan area. In addition, the research also uses interview and observation methods. This research is expected to reveal the forms of power relations of several kings who issued inscriptions for the Tamblingan region. The theories used are deconstruction theory, power relation theory, hermeneutic theory, and discourse theory. In these inscriptions power relations occur in social, economic, religious and social aspects. The ideologies are economic ideology, political ideology and knowledge ideology. Keywords : power relations, Tamblingan inscriptions, ideology